Pelatihan Manajemen Kelas Efektif guna Meningkatkan Kualitas Pembelajaran pada Era Merdeka Belajar: Effective Classroom Management Training to Improving Learning Quality in the Merdeka Belajar Era’s - Syahroni, Mashud; Suwidagdho, Dhanang; Hananto, Ipung (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Class management is one of the supporting aspects of the good learning process. Good management produces a conducive learning environment for both students and teachers. The new learning paradigm in the Merdeka Belajar curriculum means that teachers, as learning leaders, must be able to create safe, comfortable, and enjoyable classes. The problem with partners is that classroom management still needs to be optimal because teachers' knowledge and understanding regarding effective classroom management are not optimal. Teacher's understanding of effective classroom management is arranging students' seats. The psychological approach of students still needs to be fully understood and implemented by teachers in classroom management. The Universitas Tidar community service team is trying to solve problems at the two partners through an effective classroom management training program. Class management is physical and managing students and their social learning environment. Therefore, training is needed to improve classroom management skills effectively. The subjects of this training were teachers at SMP Negeri 3 and SMP Negeri 9 Kota Magelang. The approach used is a classical approach. The method of implementing service activities is through lectures and discussions. The results of service activities are that teachers gain new knowledge regarding effective classroom management, and teachers' skills increase in managing classes according to student's needs.